2004
DOI: 10.1111/j.1399-5618.2004.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar disorder. III: Harm avoidance a risk factor for suicide attempts

Abstract: Age of onset, HA, PS, gender and family history of suicide had a moderate to very strong effect on suicide attempts in bipolar patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 43 publications
3
42
1
2
Order By: Relevance
“…In the group of suicide attempters, we found significantly higher scores on HA and significantly lower scores in SD, CO, and PS when compared to the non-suicidal group. Previous studies found results somewhat similar to ours, i.e., higher HA and lower SD in the group of patients with mood disorders who had suicide attempt (see Woo et al 2014, Brezo et al 2006, Engstrom et al 2004). Higher HA, defined as a tendency to respond intensely to signals or aversive stimuli, may be state-dependent personality trait in depressive states (Pelissolo & Corruble 2002).…”
Section: Discussionsupporting
confidence: 74%
“…In the group of suicide attempters, we found significantly higher scores on HA and significantly lower scores in SD, CO, and PS when compared to the non-suicidal group. Previous studies found results somewhat similar to ours, i.e., higher HA and lower SD in the group of patients with mood disorders who had suicide attempt (see Woo et al 2014, Brezo et al 2006, Engstrom et al 2004). Higher HA, defined as a tendency to respond intensely to signals or aversive stimuli, may be state-dependent personality trait in depressive states (Pelissolo & Corruble 2002).…”
Section: Discussionsupporting
confidence: 74%
“…Confirming the validity of our results, we found that harm avoidance was the only temperament associated with suicide risk. This link has been previously reported as a predisposing factor for suicide (Engstrom et al, 2004).…”
Section: Profile Of Prisoners With a Dd Compared To Other Prisonerssupporting
confidence: 63%
“…When compared to healthy individuals, bipolar patients achieve higher scores on novelty seeking (Young et al, 1995;Osher et al, 1999;Evans et al, 2005), harm avoidance (Young et al, 1995;Osher et al, 1996;Engstrom et al, 2004a;Evans et al, 2005) and reward dependence (Osher et al, 1996), and lower scores on persistence (Osher et al, 1996;Osher et al, 1999) and self-directedness (Engstrom et al, 2004a;Evans et al, 2005). In bipolar disorder, higher scores on harm avoidance were also associated with early onset of disease and fewer suicide attempts (Engstrom et al, 2003;Engstrom et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%